Derive the following equations of motion

a) v=u + at
b)
[tex]s = ut + \frac{1}{2} {}at^{2} [/tex]
c)
[tex]v {}^{2} = {u}^{2} + 2as[/tex]
plz help me

Respuesta :

Answer:

___________________________________

a. Let us assume a body has initial velocity 'u' and it is subjected to a uniform acceleration 'a' so that the final velocity 'v' after a time interval 't'. Now, By the definition of acceleration, we have:

[tex]a = \frac{v - u}{t} \\ or \: at = v - u \\ v = u + at \: [/tex]

It is first equation of motion.

___________________________________

b. Let us assume a body moving with an initial velocity 'u'. Let it's final body 'v' after a time interval 't' and the distance travelled by the body becomes 's' then we already have,

[tex]v = u + at...........(i) \\ s = \frac{u + v}{2} \times t.........(ii)[/tex]

Putting the value of v from the equation (i) in equation (ii), we have,

[tex]s= \frac{u + (u + at)}{2} \times t \: \: \\ or \: s = \frac{(2u + at)t}{2} \\ or \: s = \frac{2ut + a {t}^{2} }{2} \\ s = ut + \frac{1}{2} a {t}^{2} [/tex]

It is third equation of motion.

________________________________

c. Let us assume a body moving with an initial velocity 'u'. Let it's final velocity be 'v' after a time and the distance travelled by the body be 's'. We already have,

[tex]v = u + at.....(i) \\ s = \frac{u + v}{2} \times t......(ii) \\ [/tex]

[tex]v = u + at \\ or \: at = v - u \\ t = \frac{v - u}{a} [/tex]

Putting the value of t from (i) in the equation (ii)

[tex]s = \frac{u + v}{2} \times \frac{v - u}{a} \\ or \: s = \frac{ {v}^{2} - {u}^{2} }{2a} \\ or \: 2as = {v}^{2} - {u}^{2} \\ {v}^{2} = {u}^{2} + 2as[/tex]

It is forth equation of motion.

________________________________

Hope this helps...

Good luck on your assignment..